2017
DOI: 10.1103/physrevlett.118.097801
|View full text |Cite
|
Sign up to set email alerts
|

Combining Diffusion NMR and Small-Angle Neutron Scattering Enables Precise Measurements of Polymer Chain Compression in a Crowded Environment

Abstract: The effect of particles on the behavior of polymers in solution is important in a number of important phenomena such as the effect of "crowding" proteins in cells, colloid-polymer mixtures, and nanoparticle "fillers" in polymer solutions and melts. In this Letter, we study the effect of spherical inert nanoparticles (which we refer to as "crowders") on the diffusion coefficient and radius of gyration of polymers in solution using pulsed-field-gradient NMR and small-angle neutron scattering (SANS), respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 37 publications
2
17
1
Order By: Relevance
“…We can use the fitted results to recast all the measurements of polymer self-diffusion in charged Ficoll70 (colored symbols), as well as the previous results with uncharged As discussed in Sec. II and in previous work in the presence of an uncharged crowder, 21 such an exponential relationship could be consistent with the theory for atomic liquids where an exponential relationship between atomic diffusion and the excess entropy is predicted. 33,34 Such a remarkably universal exponential dependence at all Φ F , and independent of crowder charge, suggests that above c , only the structure is important, and colloidal hydrodynamics is unimportant.…”
Section: Polymer Self-diffusivity In Charged Crowdersupporting
confidence: 89%
See 3 more Smart Citations
“…We can use the fitted results to recast all the measurements of polymer self-diffusion in charged Ficoll70 (colored symbols), as well as the previous results with uncharged As discussed in Sec. II and in previous work in the presence of an uncharged crowder, 21 such an exponential relationship could be consistent with the theory for atomic liquids where an exponential relationship between atomic diffusion and the excess entropy is predicted. 33,34 Such a remarkably universal exponential dependence at all Φ F , and independent of crowder charge, suggests that above c , only the structure is important, and colloidal hydrodynamics is unimportant.…”
Section: Polymer Self-diffusivity In Charged Crowdersupporting
confidence: 89%
“…In a recent study, 21 we have shown that the uncharged Ficoll70 crowder induces little compression in the polymer, consistent with a simulation that assumes hard-sphere crowders; 22 this suggests that Ficoll70 does not associate, and is thus an inert crowder, at least with respect to PEG. However, it is unclear whether an uncharged, hard-sphere crowder is relevant to real biophysical situations, such as macromolecular crowding in living cells where the macromolecules are charged entities, such as proteins and nucleic acids.…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…With the recent advances of its derivative techniques, i.e., grazing-incidence [3], anomalous [4], scanning [5] or magnetic [6] SAS, the range of applications has been greatly extended. This includes now a much larger class of hierarchical materials, i.e., materials in which the structural elements themselves have a structure, such as biological macromolecules [1,[7][8][9], polymers [10][11][12][13], composites [14][15][16][17] or cellular solids [18][19][20].…”
Section: Introductionmentioning
confidence: 99%